Positivity in Younger and in Older Age: Associations With Future Time Perspective and Socioemotional Functioning - Erbey, Miray; Roebbig, Josefin; Babayan, Anahit; Kumral, Deniz; Reinelt, Janis; Reiter, Andrea M. F.; Schaare, Lina; Uhlig, Marie; Nierhaus, Till; Van der Meer, Elke; Gaebler, Michael; Villringer, Arno (Frontiers in Psychology, 2020)
Aging has been associated with a motivational shift to positive over negative information (i.e., positivity effect), which is often explained by a limited future time perspective (FTP) within the framework of socioemotional selectivity theory (SST). However, whether a limited FTP functions similarly in younger and older adults, and whether inter-individual differences in socioemotional functioning are similarly associated with preference for positive information (i.e., positivity) is still not clear. We investigated younger (20–35 years, N = 73) and older (60–75 years, N = 56) adults’ gaze preferences on pairs of happy, angry, sad, and neutral faces using an eye-tracking system. We additionally assessed several parameters potentially underlying inter-individual differences in emotion processing such as FTP, stress, cognitive functioning, social support, emotion regulation, and well-being. While we found no age-related differences in positivity when the entire trial duration was considered, older adults showed longer fixations on the more positive face in later stages of processing (i.e., positivity shifts). This allocation of resources toward more positive stimuli might serve an emotion regulatory purpose and seems consistent with the SST. However, our findings suggest that age moderates the relationship between FTP and positivity shifts, such that the relationship between FTP and positivity preferences was negative in older, and positive in younger adults, potentially stemming from an age-related differential meaning of the FTP construct across age. Furthermore, our exploratory analyses showed that along with the age and FTP interaction, lower levels of worry also played a significant role in positivity shifts. We conclude that positivity effects cannot be solely explained by aging, or the associated reduced FTP per se, but is rather determined by a complex interplay of psychosocial and emotional features.